2007
DOI: 10.1111/j.1532-950x.2007.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biomechanical Properties of Linear, Circular, and Hybrid External Skeletal Fixation Devices for Use in Large Ruminants

Abstract: The model II DAF made of low carbon steel was economical and may be useful for treating long bone fractures in large ruminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Fixator rigidity depends on the design and the material used to construct the fixator (Johnson and DeCamp, 1999;Singh et al, 2007). Generally the fixator constructs are made of stainless steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixator rigidity depends on the design and the material used to construct the fixator (Johnson and DeCamp, 1999;Singh et al, 2007). Generally the fixator constructs are made of stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the acrylic fixator is stronger in axial, craniocaudal and torsional loads and as strong in mediolateral bending loads compared with stainless steel fixator (Willer et al, 1991). The biomechanical property of a fixator system is influenced by the size and number of fixation pins, design and the material used to construct the fixator, hence it varies among different fixator constructs (Anderson and St. Jean, 1996;Singh et al, 2007;Tyagi et al, 2014). The purpose of this study was to evaluate and compare the fixators on the basis of points of support (2-points support per segment and with 3-points support point per segment), the number of pins used, the type of material used for construction (acrylic v/s epoxy) and design of the constructs like uniplanar, multiplanar and circular.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of ESF devices are weight‐bearing ability immediately after surgery, normal joint mobility, and an optimal environment for osteosynthesis and wound healing without the need for an implant in the fracture site 11 . For large animal use, ESF devices must be sufficiently rigid, well tolerated, and easily applied 12 …”
Section: Introductionmentioning
confidence: 99%
“…Schanz pins are easy to apply, cause minimal soft tissue lesions, and provide adequate fixation in the diaphysis. Tensioned wires enable the fixation of periarticular fragments, even small ones, without compromising joint mobility 11,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation